2018
DOI: 10.22159/ijap.2017.v9s2.01
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Propolis Fluoride Application in Inhibiting Dental Caries Activity in School Children Age 6-9 Years Old

Abstract: Objective: To obtain the effectiveness of propolis fluoride application in inhibiting dental caries activity. Methods:The study was included 170 children aged 6-9 years old with active dentinal carries surface was 532 tooth surfaces, all of 532 tooth surface will applicate use propolis fluoride in school children at primary school SD Kukusan. Evaluation of the amount of dentinal caries lesion that has been arrested was conducted after 1 month, 2 months, and 4 months after topical application. Results:After pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…To test the efficiency of propolis in inhibiting dental caries, propolis fluoride was applied to children's teeth with active dentinal carries surface. Carries were stopped in 99.80% of the cases after just one month of application without causing any black discoloration of the teeth [137]. In another study, researchers treated patients suffering from chronic periodontitis with an irrigation of the selected sites with a hydro alcoholic solution of propolis extract propolis.…”
Section: Antibacterial Activity Of Propolismentioning
confidence: 99%
“…To test the efficiency of propolis in inhibiting dental caries, propolis fluoride was applied to children's teeth with active dentinal carries surface. Carries were stopped in 99.80% of the cases after just one month of application without causing any black discoloration of the teeth [137]. In another study, researchers treated patients suffering from chronic periodontitis with an irrigation of the selected sites with a hydro alcoholic solution of propolis extract propolis.…”
Section: Antibacterial Activity Of Propolismentioning
confidence: 99%
“…India Topical application of Propolis fluoride (PPF) solution also has the similar advantage of causing no black discoloration to the teeth. Darwita et al [49] reported that PPF was effective in inhibiting dentinal caries till three months post-application. They stated that it should be repeated after 3 months to continue the preventive effect.…”
Section: ) Sdf+lasermentioning
confidence: 99%
“…Dental caries is a disease that affects many children and adults, may affects deciduous and permanent teeth [5,6]. The prevalence of dental and oral health problems based on the age category were about 10.4% of children aged 1-4 y, 28.9% of children aged 5-9 y and 25.2% of children aged 10-14 y, and only about 25.8%, 35.1%, and 28.3% consecutively, were treated [7].…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries has a high financial burden on parents of affected children [10]. In high-income countries, dental treatment is costly with 5% of the total health expenditure and 20% of out-of-pocket health expenditure [11].…”
Section: Introductionmentioning
confidence: 99%